Case study successful use of stent graft in post-catherization massive pseudoaneurysm of femoral artery with wide neck - Kunwar, Brajesh Kumar; Ingle, Farah; Ingle, Atul; Tulasigeri, Chandrasekhar (International Journal of Research in Medical Sciences, 2021)
Pseudoaneurysms are not rare and can occur due to varied reasons including percutaneous vascular access. If left untreated, pseudoaneurysms can be fatal. Here, we have presented a classic case study where a large pseudoaneurysm of left femoral artery with very wide neck was closed using stent graft. A 55 years old male was presented with severe painful large mass in left groin. The mass was soft tissue swelling with severe tenderness and pulsatile in nature. The doppler suggested it to be filled with blood and communicating with femoral artery hence diagnosed as pseudoaneurysm. Attempt was made to compress the neck which was large not clearly defined, hence failed. Multiple interventional and surgical options of closure of pseudoaneurysm was discussed. Patient was taken for stent graft deployment in cath lab. Check angiogram showed nicely flowing femoral artery with no signs of pseudoaneurysm. The patient immediately improved with decrease in pain and swelling.